Thinking about Thinking: Beyond Decision-Making Rationalism and the Emergence of Behavioral Ethics. (18th January 2018) - Bowman, James S.
Abstract : This article examines behavioral ethics propositions, cognitive distortions, and bias reduction techniques. This is followed by the practitioner and academician response of the public administration profession to this nascent, intriguing field. The purpose is to review critical components of behavioralism and to examine the present status of behavioral decision science in the practice and study of public service ethics. How people think about thinking is important, because to address problems effectively, there must be an understanding of why individuals believe what they believe, how they think about issues, and why decisions are made.